2016
DOI: 10.1139/cjfas-2015-0402
|View full text |Cite
|
Sign up to set email alerts
|

Genetic stock composition of marine bycatch reveals disproportional impacts on depleted river herring genetic stocks

Abstract: Bycatch of mid-trophic-level anadromous fishes that connect marine and freshwater ecosystems is a growing conservation concern. Anadromous alewife (Alosa pseudoharengus) and blueback herring (Alosa aestivalis) are important components of coastal freshwater and marine food webs, but have experienced dramatic declines in the abundances of spawning adults. Freshwater-focused restoration efforts have yielded few consistent signs of recovery, raising concerns that bycatch in Northwest Atlantic commercial fisheries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 63 publications
(89 reference statements)
2
50
0
Order By: Relevance
“…With this increased resolution, assignment accuracy has remained high, averaging 88%–91% for individual assignment or mixture analysis, respectively, on par with previous estimates of regional assignment accuracy in salmon populations in eastern North America (Bradbury et al., ; Gauthier‐Ouellet et al., ; Moore et al., ). Notwithstanding the high overall accuracy reported here, slight systematic biases either upward or downward were detected in assignment among a few reporting groups as has been noted elsewhere (Hasselman et al., ), but these biases seem to have minimal impact on the levels of overall accuracy.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…With this increased resolution, assignment accuracy has remained high, averaging 88%–91% for individual assignment or mixture analysis, respectively, on par with previous estimates of regional assignment accuracy in salmon populations in eastern North America (Bradbury et al., ; Gauthier‐Ouellet et al., ; Moore et al., ). Notwithstanding the high overall accuracy reported here, slight systematic biases either upward or downward were detected in assignment among a few reporting groups as has been noted elsewhere (Hasselman et al., ), but these biases seem to have minimal impact on the levels of overall accuracy.…”
Section: Discussionsupporting
confidence: 80%
“…Hasselman et al. () have shown that use of the parametric bootstrap correction as implemented in RUBIAS reduces biases in mixed‐stock estimates by >50%. For each fishery sample, we estimate the proportion contributed from each reporting unit, and the 95% credible interval from MCMC samples of the mixing proportions of the posterior probability distribution.…”
Section: Methodsmentioning
confidence: 99%
“…Generating these markers using high‐throughput sequencing of genomic DNA enhances our ability to confidently distinguish populations of alewife and blueback herring that are genetically distinct across both species’ ranges. This ability to identify stock of origin for fish caught at sea is critical for management of populations experiencing diminished spawning returns and of increasing conservation concern (Hasselman et al., ). Using these new tools, samples from mixed‐stock assemblages can be quickly and efficiently genotyped, allowing new insights into marine movement patterns and impacts of marine fisheries.…”
Section: Discussionmentioning
confidence: 99%
“…Hasselman et al. () also found that these same data had sufficient statistical power to confidently assign river herring bycatch in commercial fisheries to regional genetic stocks. Given their propensity for natal philopatry, the conservation and management of river herring requires a “population‐level” approach, and there is a need for molecular tools that can resolve population genetic structure at spatial scales finer than regional genetic stock.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation